A Comparative Analysis of the Legal Framework on Electronic Waste Management in Nigeria, Japan, EU and India - Ibrahim, Ibrahim Bello; Anigbogu, Bridget (ABUAD Law Journal, 2025)
Rapid increase in the number of electronic devices produce yearly in recent times has led to significant global environmental challenges like rapid increase in electronic waste (e-waste), due to electronics short lifespan. The improper handling, recycling, and disposal of e-waste pose substantial environmental and public health hazards due to the presence of toxic substances and the potential for resource depletion. This article presents a comparative analysis of e-waste management in legal frameworks in Nigeria, the European Union (EU), Japan, and India, the selection of these jurisdictions provides a diverse perspective, with the EU representing a regional approach, Japan technologically advanced nation, and India and Nigeria highlighting the challenges faced by developing nations. The analysis examines the strength and weakness if existing legislations, focusing on the implementation of Extended Producer Responsibility (EPR), the integration of the informal sector, and enforcement of regulations. The study reveals that while the EU and Japan have established comprehensive legal frameworks and advanced management practices, Nigeria and India struggle with implementation challenges and large informal sector. The article concludes by advocating for stronger, specific e-waste legislation, formalizing the informal sector, effective EPR implementation, and increased public awareness, particularly in Nigeria.